2014
DOI: 10.4103/1995-705x.151089
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical coronary artery embolism - A rare cause of myocardial infarction

Abstract: Paradoxical coronary artery embolism is a rare, but often an underdiagnosed cause of acute myocardial infarction. It should be considered in patient who presents with chest pain and otherwise having a low risk profile for atherosclerosis coronary artery disease. We describe a case of paradoxical coronary artery embolism causing ST segment elevation myocardial infarction in a patient with upper extremity venous thrombosis. Echocardiography demonstrated a patent foramen ovale (PFO) with bidirectional shunt. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
(4 reference statements)
0
17
0
2
Order By: Relevance
“…[12] A study by Hakim et al (2014) highlighted the importance of having high index of suspicion for paradoxical embolism in patients who have myocardial infarction in the absence of traditional cardiovascular risk factors. [13] This perspective is applicable to our patient despite his presumed genetic predisposition to hypercoagulability. The study asserted that 10–15% of all paradoxical emboli are responsible for paradoxical coronary embolism.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[12] A study by Hakim et al (2014) highlighted the importance of having high index of suspicion for paradoxical embolism in patients who have myocardial infarction in the absence of traditional cardiovascular risk factors. [13] This perspective is applicable to our patient despite his presumed genetic predisposition to hypercoagulability. The study asserted that 10–15% of all paradoxical emboli are responsible for paradoxical coronary embolism.…”
Section: Discussionmentioning
confidence: 89%
“…The study asserted that 10–15% of all paradoxical emboli are responsible for paradoxical coronary embolism. [13]…”
Section: Discussionmentioning
confidence: 99%
“…1 Paradoxical coronary embolism is rare and accounts for only 10% to 15% of paradoxical emboli events. 2 It should be suspected in young individuals at low risk for atherosclerotic disease and without other risk factors for coronary thrombosis such as oral contraceptive use and polycythemia. The management of paradoxical coronary embolism is highlighted in this case, which includes aspiration thrombectomy with or without angioplasty and aggressive anticoagulation management.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in an era of widespread use of antibiotics, coronary emboli from IE do still occur, and can present as ST-elevation myocardial infarction [25]. Studies have shown microemboli in the coronary arteries in 60% of patients with IE [25][26][27].…”
Section: Streszczeniementioning
confidence: 99%
“…The diagnosis of IE has serious implications for the proper choice of therapeutic method in case of CE. There are several reports that warn about use of thrombolysis for AMI associated with endocarditis, due to risk of fatal intracranial bleeds and massive gastrointestinal bleeding [25][26][27][28][29].…”
Section: Streszczeniementioning
confidence: 99%